Influencia y actividad musical de los salesianos en Salamanca a comienzos del s. XX = Salesian´s Influence and Musical Activity in Salamanca at the Beginning of the 20th Century - Álvarez García, Francisco José (Cauriensia, 2024)
The current article examines the significant musical contributions of band entities associated with the Salesian Congregation in the city of Salamanca, Spain, during the early years of the 20th century. Through a historical-analytical methodological approach and supported by references from the local press, the evolution and impact of the three groups promoted by the congregation, reference points in the city of Tormes for the musical and religious environment of the time, are traced: the band from the Calatrava seminary, directed by Miguel Rodríguez; the band from the Protectorate of Young Industrialists; and the one known as Salesiana. These institutions, founded on the pedagogical and cultural principles of Don Bosco, emerged and expanded within the community structure of Salamanca, a city still of modest dimensions at that time. The research marks an interval of eleven years, a time during which the musical groups established themselves as pillars in local music education and culture, transcending beyond a mere playful and musical exercise. The contributions of these bands represent a lasting legacy that continues to influence the educational, religious, and musical identity of the region.